2001
DOI: 10.1016/s0014-2921(00)00083-0
|View full text |Cite
|
Sign up to set email alerts
|

Growth effects of government expenditure and taxation in rich countries

Abstract: A number of cross-country comparisons do not find a robust negative relationship between government size and economic growth. In part this may reflect the prediction in economic theory that a negative relationship should exist primarily for rich countries with large public sectors. In this paper an econometric panel study is conducted on a sample of rich countries covering the 1970-95 period. Extended extreme bounds analyses are reported based on a regression model that tackles a number of econometric issues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
260
1
15

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 438 publications
(292 citation statements)
references
References 24 publications
(23 reference statements)
16
260
1
15
Order By: Relevance
“…If resources were allocated less efficiently by larger governments, economic growth would be hindered. This conjecture is supported by several existing works (e.g., Landau, 1985;Peden & Bradley, 1989;Fölster & Herekson, 2001). On the other hand, some studies do not find an obvious association between government size and economic growth (e.g., Ram, 1986;Bairam, 1990;Easterly and Rebelo, 1993;Mendoza et al, 1997).…”
Section: Introductionsupporting
confidence: 75%
“…If resources were allocated less efficiently by larger governments, economic growth would be hindered. This conjecture is supported by several existing works (e.g., Landau, 1985;Peden & Bradley, 1989;Fölster & Herekson, 2001). On the other hand, some studies do not find an obvious association between government size and economic growth (e.g., Ram, 1986;Bairam, 1990;Easterly and Rebelo, 1993;Mendoza et al, 1997).…”
Section: Introductionsupporting
confidence: 75%
“…There are many studies that have examined the effect of taxes on economic growth (Helms, 1985;Myles, 2000;Folster and Henrekson, 2001;Lee and Gordon, 2005;Tosun and Abizadeh, 2005;Bania et al 2007;Furceri and Karras, 2007;Reed, 2008;Romer and Romer, 2010;Gemmel et al 2011;Arnold et al 2011;Barro and Redlick, 2011;Ferede and Dahlby, 2012;Mertens and Ravn, 2013;Saqib et al 2014;Gale et al 2015;Ojong et al 2016). Engen and Skinner (1996) found that 2.5% point increase in tax to GDP ratio decreases GDP growth by 0.2-0.3%.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Thus, for instance, some of those studies have found that aggregate public spending is associated negatively with economic growth [Landau (1986); Levine and Renelt (1992); Folster et al (2001); Schaltegger and Torgler (2004)], while others have found the opposite relationship [Ram (1986);Sattar (1993); Bose, Haque and Osborn (2003)]. Even, the neutrality of public expenditure on economic growth is claimed [Kormendi and Maguire (1985)].…”
Section: Previous Literaturementioning
confidence: 99%
“…al. (2003); Folster and Henrekson (2001); Schaltegger and Torgler (2004)]; nuanced, in that depending on the types of expenditures analyzed the results point to different levels of inefficiency. The case for developing countries might be much different.…”
Section: Introductionmentioning
confidence: 99%